Interpretação do espaço social da Região Histórica das Missões Jesuítico-Guarani: uma dialética com as reflexões do francês Guy Di Méo - Muriel Pinto (Confins)
The study of social spaces requires critical thinking, since territorial support for complex discussions, as the social arrangements, cultural practices and urban identity narratives. Thus, these contribute to the construction of memory spaces, as they are constantly engaged in dialogue with the past. The historic region of Jesuit Missions-Guarani has a diverse heritage. Currently these cultural assets, are being better planned by national and international bodies. However, the lack of studies focused on the analysis of the construction of the missionary identity and its relations with the transformations of space. The article focused on analyzing the missionary identity construction from the interpretation of regional landscapes, to reflect on the Constitution of social spaces. It was used as a theoretical matrix reflections of the french thinker Guy Di Méo. The study is notable for proposing the discussion a vision not for the identity not missions, because the research can identify various socio-spatial identities sin the region. It should be noted that the thoughts of Guy Di Meo contributed to the integration of concepts between, identity, heritage, social spaces, landscapes, and tourism. What proposes an innovative vision for the Cultural Geography of the Missions.